Fully Fibrous Large‐Area Tailorable Triboelectric Nanogenerator Based on Solution Blow Spinning Technology for Energy Harvesting and Self‐Powered Sensing. Issue 37 (10th August 2022) - Xu, Huayu; Tao, Juan; Liu, Yue; Mo, Yepei; Bao, Rongrong; Pan, Caofeng
Abstract: An all‐fibrous large‐area (20 × 50 cm 2 ) tailorable triboelectric nanogenerator (LT‐TENG) is prepared using a one‐step solution blow spinning technology, which has the advantages of easy operation, scale‐up in the area, and high production efficiency. The prepared LT‐TENG is composed of polyvinylidene fluoride (PVDF)/MXene (Ti3 C2 T x ) nanofibers (NFs) and conductive textile. Benefiting from the fibrous materials and large‐area properties, the LT‐TENG possesses the merits of good tailorability, breathability, hydrophobicity, and washability. When optimized by mixing the MXene into PVDF NFs, the LT‐TENG has a preferable output and sensing property, with a detection range over 16 kPa and a relatively high sensitivity of 12.33 V KPa −1 . At maximum applied pressure, the voltage, current, and charge are 108 V, 38 µA, and 35 nC, respectively. This LT‐TENG can serve as a biomechanical energy harvester when used as wearable devices with an output power density of 12.6 mW m −2 at an external load resistance of 500 MΩ, and it also has the ability of self‐powered tactile sensing for pressure mapping and slide sensing. Thus, this LT‐TENG exhibits great potential prospects in wearable devices, intelligent robots, and human–machine interaction. Abstract : A fully fibrous large‐area triboelectric nanogenerator (TENG) based on solution blow spinning technology is designed for this work. The TENG is tailorable, breathable, and hydrophobic. It can be used for bioenergy harvesting and self‐powered sensing. Thus, the TENG has high application value in the field of wearable devices.